Cara Pemilihan Strategi Kendali Laju dan Irama - Dicky A Hanafy (The Indonesian Heart Association, 2010)
Atrial fibrillation (AF) is common and highly variable in its clinical presenta-tion and evolution. Iit causes substantial morbidity and mortality, including impaired quality of life, heart failure, systemic emboli, and stroke. An ac-curate diagnosis is important and should be distinguished from atrial flutter or other arrhythmias which involves the atrium. Management of patients with AF involves 3 objectives: rate control, rhythm control, and prevention of thromboembolism. A rate control strategy alone, without attempts at restoration or maintenance of sinus rhythm (SR), is reasonable in some patients with AF, especially those who are asymptomatic. In some circum-stances, when the cause of AF is reversible, such as when AF occurs after cardiac surgery, no long-term therapy may be necessary. The CHADS2 scoring system can be used to risk stratify patients with nonvalvular AF to determine the need for warfarin. The risk of thromboembolism or stroke does not differ between pharmacological and electrical CV. Ablation of the AV conduction system and permanent pacing is an option for patients with rapid ventricular rates despite maximum medical therapy. However, there is growing concern about the negative effects of long-term RV pac-ing. Biventricular pacing may overcome many of the adverse hemodynamic effects associated with RV pacing. Pharmacological therapy to maintain SR should be considered in patients who have troublesome symptoms. Drugs should be used to decrease the frequency and duration of episodes, and to improve symptoms. AF recurrence while taking an antiarrhythmic drug is not indicative of treatment failure and does not necessitate a change in antiarrhythmic therapy. Antiarrhythmic drug choice is based on side effect profiles and the presence or absence of structural heart disease, heart failure, and hypertension. Catheter ablation for AF is currently considered a second-line therapy in highly symptomatic patients in whom one or more antiarrhythmic agents have failed.